Dive Tourism and Local Communities: Active Participation or Subject to Impacts? Case Studies from Malaysia - Daldeniz, Bilge; Hampton, Mark P. (The international journal of tourism research, 2013)
ABSTRACT Dive tourism impacts were examined in three Malaysian islands: Perhentian (backpackers), Redang (package tourism) and Mabul (upmarket dive tourism). Qualitative local participation approaches were applied to investigate whether host communities were merely reactive to dive tourism's impacts. Dive tourism affected many aspects of community life. Besides physical/ environmental impacts (new infrastructure), research found varied economic impacts including employment/business opportunities and differing economic linkages. Participation varied between locations, and obstacles to increased participation were revealed. Mainly negative socio‐cultural impacts were observed with minimal participation in cultural productions (handicrafts, performances). However, positive educational impacts emerged, especially environmental awareness and English language acquisition. Copyright © 2012 John Wiley & Sons, Ltd.